Infant Warmer Design with PID Control for Stability and Equal Temperature Distribution Equipped with Digital Scales for Prevention of Hypothermia in Newborns - Ishika Sharma; Monika Singh (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2021)
Babies need temperatures that match the temperature in the mother's womb, which is between 35°C – 37°C. the latest research on infant warmer equipment uses the fuzzy method as a system for temperature control in infant warmers, The problem in previous research is that at each temperature setting, the temperature is not evenly distributed throughout the bed, when it reaches the setting temperature, the heater continues to turn on so that the bed gets hotter. The purpose of this research is to make an infant warmer equipped with digital scales, with temperature settings of 350C, 360C, and 370C using PID control to stabilize the temperature and ensure the spread of heat on the bed evenly, then the addition of skin temperature aims to make nurses know what the patient's body temperature is when observations were made. The infant warmer in this module uses an arduino microcontroller which is displayed in 7segment, then the skin sensor used is the DS18B20 temperature sensor to read the skin temperature, and the infant warmer temperature sensor used is LM35 as a PID control system. The results of the research in making the tool module were compared with the measurement results against the comparator. This research has obtained the results of the smallest error in the measurement of setting temperature of 350C with an error of 0%. For comparison with the incu analyzer, the smallest error is obtained at the setting temperature of 370C with an error value of 0% on the T5 measurement, the difference in skin temperature against the thermometer is 0.10C. The results showed that the temperature spread on the module had different error values. So that this research can be implemented on the PID control infant warmer system to improve performance on infant temperature stability.